The Effect of Religious Music Therapy on Blood Pressure Changes in Elderly with Hypertension - Henry Sudiyanto; Siti Rachma; Dian Irawati; Fikri Nur Hamzah (STIKes Patria Husada Blitar, 2023)
Hypertension or high blood pressure is a non-communicable disease most suffered elderly. It is characterized by increasing the pressure of blood vessels. Music therapy is one of non-pharmacological management on hypertension so it can be controlled to improve quality of life the patient.The study aimed to analyze the effect of religious music therapy on blood pressure changes in elderly with hypertension. The study design wasÂ quasy experiment with a pre-post test approach. Sample of 25 respondents was taken by purposive sampling and carried out at Unit Pelayanan Teknis (UPT) Pesanggrahan Penyandang Masalah Kesejahteraan Sosial (PMKS) Mojopahit Mojokerto. Data analyzed by paired T-test. The results showed a pre-test systolic mean of 156.12 mmHg and a post-test of 149.9 mmHg with a p value of systolic = 0.00 (p <0.05) and a pre-test mean diastolic of 95.76 mmHg and a post-test of 89.40 mmHg with a diastolic p value = 0.00 (p < 0.00). It means that was an effect of religious music therapy on reducing blood pressure in hypertensive elderly at UPT Pesanggrahan PMKS Mojopahit. When music therapy was heard, the brain will produce endorphins that relieves anxiety and tension, so it decrease blood pressure. The recommendation of this study was religious music therapy can be chosen as non-pharmacological management to control elderlyâ€™s blood pressure